1996
DOI: 10.1007/bf02359413
|View full text |Cite
|
Sign up to set email alerts
|

Distinctions in the neuronal activity of the rabbit limbic cortex under different training strategies

Abstract: Limbic cortex neurons as well as the temporal characteristics of the behavioral cycles were recorded in rabbits trained to perform a food-procuring behavior according to different strategies which were distinguished by the sequence of the stages of training. It was demonstrated that additional activations can appear in the nonspecific activity of neurons specialized relative to one of those behavioral acts for which the animal was trained directly in the experimental cage. Such activations appeared, depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Such reorganization could develop in a similar way across the animals of "mismatch" group due to the identity of their training history. Patterns of task-related neuronal activations in the cortex were shown to depend on the previous training history [12] [57]. All the mentioned data and our results are in a line with suggestion that during the first stage of learning-"mismatch" stage-previously learned behaviors and previously acquired neuronal ensembles are temporary reorganized; this process was called "accommodative reconsolidation" [58].…”
Section: Discussionsupporting
confidence: 90%
“…Such reorganization could develop in a similar way across the animals of "mismatch" group due to the identity of their training history. Patterns of task-related neuronal activations in the cortex were shown to depend on the previous training history [12] [57]. All the mentioned data and our results are in a line with suggestion that during the first stage of learning-"mismatch" stage-previously learned behaviors and previously acquired neuronal ensembles are temporary reorganized; this process was called "accommodative reconsolidation" [58].…”
Section: Discussionsupporting
confidence: 90%
“…It was shown in our laboratory that there were significant differences of neuronal activations in what seemed to be the same instrumental foodacquisition behavior of animals taught to perform the successive acts of this behavior in various orders (Alexandrov et al, 2000;Gorkin & Shevchenko, 1996). It has also been found in our laboratory that the number of neurons active in what was apparently the same behavior depends on the number of steps required to learn this behavior (Gavrilov et al, 2007).…”
Section: Brain Subserving Of Behavior Reflects the History Of Its Formation; Hence The Activation Characteristics And Sets Of Active Neurmentioning
confidence: 65%
“…It was shown that later-formed behaviour is subserved by the activity of a higher quantity of neural networks [ 20 , 21 , 47 ]. Therefore, we assume that when an individual is performing a later formed behaviour, his heart is involved in a more complex non-linear activity in order to achieve an adaptive coordination with the activity of neuronal elements of functional systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the system organization of behaviour represents the history of behavioural development. Multiple systems are involved in behaviour, and each of them was formed at a certain stage of development of the current behaviour [ 21 ].…”
Section: Introductionmentioning
confidence: 99%